Transcriptomic Profile of the Cockle Cerastoderma edule Exposed to Seasonal Diarrhetic Shellfish Toxin Contamination - Dany Domínguez-Pérez (MDPI AG, 2021)
Bivalves constitute an important source of proteins for human consumption, but some accumulate biotoxins such as diarrhetic shellfish toxins (DSTs), constituting a risk to human health. The cockle Cerastoderma edule is one of the most important species harvested in the Portuguese coast but also one of the most affected species due to recurrent DSTs exposure. However, little is known regarding the effects of the toxins produced by blooming dinoflagellates on C. edule. Herein, we explore the Differentially Expressed Genes (DEGs) of two tissues (gills and digestive gland) from wild cockles sampled in Portugal, through their whole transcriptomic response in two different seasons (exposed and not exposed to DSTs). The de novo transcriptome assembly returned 684,723 contigs, N50 of 1049, and 98.53% completeness. Altogether, 1098 DEGs were identified, of which 353 DEGs were exclusive for the digestive gland, 536 unique for the gills and 209 DEGs were common. Among DEGs were identified known DSTs-biomarkers including glutathione peroxidase, glutathione S-transferase, superoxide dismutase, cytochrome P450, ABC transporters, actin and tubulin-related proteins, Heat shock proteins and complement C1Q-like proteins. This study provides the first transcriptomic profile of C. edule, giving new insights about its molecular responses under different environmental conditions of DSTs exposure.